The autobiography of Bertrand Russell 1914-1944: volume II - Russell, Bertrand 1872-1970 (London George Allen & Unwin, 1968)
Bertrand Russell (1872 - 1970). Philosopher, mathematician, educational and sexual reformer, pacifist, prolific letter writer, author and columnist, Bertrand Russell was one of the most influential and widely known intellectual figures of the twentieth century. In 1950 he was awarded the Noble Prize for Literature in 1950 for his extensive contributions to world literature and for his "rationality and humanity, as a fearless champion of free speech and free thought in the West."